Structural and electrical properties of SrBi2Nb2O9 thin films prepared by chemical aqueous solution at low temperature - Zanetti, S. M.; Araujo, E. B.; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 1999)
SrBi2Nb2O9 (SBN) thin films were prepared by the polymeric precursors method and deposited by dip coating onto Pt/Ti/SiO2/Si(100) substrates. The dip-coated films were specular and crack-free and crystallized during firing at 700 degrees C. Microstructure and morphological evaluation were followed by grazing incident X-ray diffraction (GIXRD), scanning electron microscopy (SEM) and atomic force microscopy (AFM). The films exhibited somewhat porous grain structure with rounded grains of about 100 nm. For the electrical measurements, gold electrodes of 300 mu m in diameter were sputter deposited on the top surface, forming a metal-ferroelectric-metal (MFM) configuration. The remanent polarization (P-r) and coercive field (E-c) were 5.6 mu C/cm(2) and 100 kV/cm, respectively. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: ferroelectric; SrBi2Ta2O9; bismuth layer; thin films; Pt/Ti/SiO2/Si substrates; perovskite phase